Simultaneous analysis of seven 2‐hydroxy fatty acids as tert‐butyldimethylsilyl derivatives in plasma by gas chromatography–mass spectrometry. (5th June 2014) - Seo, Chan; Yoon, Jaehwan; Rhee, Yumie; Kim, Jong‐Jin; Nam, Sang‐Jip; Lee, Wonjae; Lee, Gwang; Yee, Sung‐Tae; Paik, Man‐Jeong
Abstract An efficient method for the simultaneous analysis of seven 2‐hydroxy fatty acids (2‐HFAs) as tert‐butyldimethylsilyl (TBDMS) derivative was developed by gas chromatography–mass spectrometry in selected ion monitoring mode. New mass spectral data on 2‐hydroxycapric, 2‐hydroxypalmitic, 2‐hydroxystearic and 2‐hydroxybehenic acids as di‐TBDMS derivatives for hydroxyl and carboxyl groups were built. Under the optimal conditions, the present method showed a good correlation coefficient (r ≥ 0.999) in the range of 0.01–0.5 µg. The precision showed low relative standard deviation of <10%, and the accuracy (percentage relative error) varied from −5.2 to 0.3 for the seven 2‐HFAs studied. Recovery rates of all 2‐HFAs were ≥ 93.2% with good precision. When applied to normal human plasma, seven 2‐HFAs were positively identified. Therefore, the present efficient method will be useful for simultaneous analysis of 2‐HFAs in plasma. Copyright © 2014 John Wiley & Sons, Ltd.